КЫРГЫЗСТАНДАГЫ СТРУКТУРАЛЫК БИР ТЕКТҮҮ ЭМЕС РУДА КЕНДЕРДИН МАССИВДЕРИНДЕ ТАБИГЫЙ ЧЫҢАЛУУЛАРДЫН КОНЦЕНТРАЦИЯСЫ (КЫРГЫЗ РЕСПУБЛИКАСЫНЫН УЛУТТУК ИЛИМДЕР АКАДЕМИЯСЫНЫН КАБАРЛАРЫ, 2022)
The article deals with rock massifs of structurally heterogeneous ore deposits in Kyrgyzstan. The data of long-term full-scale experimental studies of the stress-strain state of rock masses are summarized and the results of diagnostics of local zones of natural stress concentrations are presented.